SAAFS: the establishment of a representative body for forensic science in South Africa. (29th July 2019) - Heyns, M.; Olckers, A.; Saayman, G.
ABSTRACT: Forensic Science practitioners in South Africa did not have a representative or a regulatory body and for many years some individuals have vocalized the need for such a representative body. In 2016, a small working group came together to take the first coordinated steps towards a body that can represent and address this need. The small working group enabled the first meeting of interested parties and established an electronic means of communication and of conducting surveys. Several issues were discussed and a steering body of five members were elected which replaced the Forensic Science Workgroup. The mandate of the Steering Committee was to establish a Constitution and Code of Ethics for the body, to arrange the founding meeting and to investigate possible affiliation with a professional council, who will have the responsibility to regulate the professionals in the field, by preparation and practice. The establishment of SAAFS was eagerly anticipated and now a reality. The management of the body, its affiliation with a professional council and the empowerment of the members are in the hands of its first duly elected officials. It is entering an exciting period of self-regulation and establishing collaborations with similar bodies in the international arena.